KAJIAN HUKUM TENTANG PERNIKAHAN DINI - Misbahul Amin, M.; Wahid, Abdurrohman (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2022)
To bridge the realization of marriage in accordance with the purpose of the marriage, the marriage law No. 1 of 1974 has determined and stipulates the basics that must be carried out in marriage. One of them is article 7 paragraph 1 which reads